The ASCIZ-DYNLL1 axis promotes 53BP1-dependent non-homologous end joining and PARP inhibitor sensitivity - Becker, Jordan R.; Cuella-Martin, Raquel; Barazas, Marco; Liu, Rui; Oliveira, Catarina; Oliver, Antony W.; Bilham, Kirstin; Holt, Abbey B.; Blackford, Andrew N.; Heierhorst, Jörg; Jonkers, Jos; Rottenberg, Sven; et al. (Nature communications, 2018)
53BP1 controls a specialized non-homologous end joining (NHEJ) pathway that is essential for adaptive immunity, yet oncogenic in BRCA1 mutant cancers. Intra-chromosomal DNA double-strand break (DSB) joining events during immunoglobulin class switch recombination (CSR) require 53BP1. However, in BRCA1 mutant cells, 53BP1 blocks homologous recombination (HR) and promotes toxic NHEJ, resulting in genomic instability. Here, we identify the protein dimerization hub—DYNLL1—as an organizer of multimeric 53BP1 complexes. DYNLL1 binding stimulates 53BP1 oligomerization, and promotes 53BP1’s recruitment to, and interaction with, DSB-associated chromatin. Consequently, DYNLL1 regulates 53BP1-dependent NHEJ: CSR is compromised upon deletion of Dynll1 or its transcriptional regulator Asciz , or by mutation of DYNLL1 binding motifs in 53BP1; furthermore, Brca1 mutant cells and tumours are rendered resistant to poly-ADP ribose polymerase (PARP) inhibitor treatments upon deletion of Dynll1 or Asciz . Thus, our results reveal a mechanism that regulates 53BP1-dependent NHEJ and the therapeutic response of BRCA1 -deficient cancers. 53BP1 is a key player in non-homologous end joining (NHEJ). Here the authors reveal an important role for the multifunctional homodimeric protein hub dynein light chain 1 (DYNLL1) in increasing the efficacy of 53BP1-mediated repair of DNA double-strand breaks (DSBs) by NHEJ.